Reliability of the Functional Auditory Performance Indicators (FAPI) to monitor progress in five-year-old children with Autism Spectrum Disorder - Kritzinger, Alta M. (Aletta Margaretha) (University of Pretoria, 2017)
Dissertation (M Communication Pathology)--University of Pretoria, 2016.